Faithful interpretations : truth and Islam in Catholic theology of religions - Geister, Philip; Hallonsten, Gösta (Islam and Catholic theology, 2021)
"Most of the essays in this volume were originally delivered as papers at a conference in Uppsala, Sweden, in October 2017, by top scholars in this evolving field. The conference had a theme of the Roman Catholic theology of religions, which in general terms makes up the subject of the foreword and the first three essays of the book, the third of which addresses Judaism specifically. The next three essays discuss the status of truth claims in Catholic and Christian theology of religions. In the final four essays of the book, the special case of Islam in relation to Christianity is specifically in focus. The concluding essay, "A Faithful Interpretation of Islam," gives the collection its name"--